Análise de erros cometidos na resolução de problemas envolvendo equações quadráticas - Tochetto, Lucinéia Regina (2022)
The present research aimed to analyze the errors made by students in solving problems involving quadratic equations. High school students from private schools participated in the research. The data collection occurred through the application of a notebook containing three questions involving quadratic equations. The data analysis was made, then, from fourteen questionnaires answered by students of the second and third series that were still following the system prior to the implementation of the new Common Curricular National Basis (CCNB). Data analysis was carried out in a qualitative way, using the error analysis methodology, taking into consideration the students’ written production in three questions with different levels of complexity. From the written production, it is possible to realize that the errors are not about finding the roots of the quadratic equations but rather interpret the statements, transcribe data into math language, algebraically manipulate the algebraic elements and execute basic arithmetic operations. To describe the errors and categorize them, several studies by other authors were used in works that involved the analysis of errors in several other mathematical topics. In this way, we conclude that the errors performed by the students are due to the lag in the previous contents that serve as a basis for learning the content about quadratic equations.